Odpowiedzi

Najlepsza Odpowiedź!
2010-03-18T21:45:54+01:00
A.
⅓x-2=x+2
1/3x-x=2+2
-2\3x=4 /:(-2/3)
x=4* (-3/2)
x=-6

b.
1-6/7x=4/7
-6/7x=-3/7 /: (-6/7)
x= -3/7* (-7/6)
x=1/2

c.
6(1/4x-2)=18
6/4x-12=18
6/4x=30 /: 6/4
x= 30* 4/6
x=20

d.
x/6-1/6=1
x/6=1 1/6
x/6=7/6 /*6
x=7

e.
-2(2x-1)=x/3
-4x+2=x/3
-4x-x/3=-2 /*3
-12x-x=-6
-13x=-6 /:(-13)
x=6/13

f.
2/5(3-x)=-2
6/5-2/5x=-2
-2/5x=-2-6/5
-2/5x= -2 6/5
-2/5x= -16/5 /(-2/5)
x= -16/5* (-5/2)
x= 8

g.
3/4(2-3x)=-6
3/2-9/4x=-6
-9/4x=-6-3/2
-9/4x= -15/2 /: (-9/4)
x= -15/2* (-4/9)
x= 10/3

h.
1/5(x-3)=9-x
1/5x-3/5=9-x
1/5x+x=9+3/5
6/5x=48/5 /:6/5
x= 48/5*5/6
x=8

i.
0,6+x/2=x+1
x/2-x=1-0,6
x/2-x= 0,4 /*2
x-x= 0,8
0=0,8
równanie nie ma rozwiązania